High glass transition temperature bismaleimide‐triazine resins based on soluble amorphous bismaleimide monomer. Issue 3 (11th September 2015) - Ren, Zhidong; Cheng, Yuanrong; Kong, Lingqiang; Qi, Tianke; Xiao, Fei
ABSTRACT A novel bismaleimide (DOPO‐BMI) with unsymmetrical chemical structure and DOPO pendant group has been prepared. The particular molecular structure makes DOPO‐BMI show an intrinsic amorphous state with a Tg about 135°C and excellent solubility in most organic solvents, which is beneficial to the processability of bismaleimide composite materials. A series of bismaleimide‐triazine (BT) resins have been prepared based on DOPO‐BMI and 2, 2‐bis(4‐cyanatophenyl)propane at various weight ratios. The prepared BT resins show outstanding solubility in organic solvent and low viscosity about 10–671 mPa s at 180°C. The cured BT resins exhibit high glass transition temperature (Tg) over 316°C. As the weight ratio of DOPO‐BMI increases to 80% (BT80), the Tg can rise to 369°C (tan δ). The cured BT resins also show good thermal stability with the 5% weight loss temperature over 400°C under both nitrogen and air atmosphere. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42882.